2011
DOI: 10.1128/jvi.02245-10
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino Acid Substitution in the Capsid of Foot-and-Mouth Disease Virus Can Increase Acid Resistance

Abstract: Foot-and-mouth disease virus (FMDV) particles lose infectivity due to their disassembly at pH values slightly below neutrality. This acid-dependent disassembly process is required for viral RNA release inside endosomes. To study the molecular determinants of viral resistance to acid-induced disassembly, six FMDV variants with increased resistance to acid inactivation were isolated. Infection by these mutants was more sensitive to drugs that raise the endosomal pH (NH 4 Cl and concanamycin A) than was infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
78
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(85 citation statements)
references
References 55 publications
7
78
0
Order By: Relevance
“…An intriguing feature of the FMDV capsid is the extreme sensitivity to acidic pH, which results in virus inactivation after exposure of virions to mildly acidic pH (8). At pH slightly below neutrality, FMDV capsid disassembles into pentameric subunits (9) and there is good correlation between loss of infectivity by in vitro exposure to acidic pH and capsid dissociation (10)(11)(12). The acid sensitivity of FMDV has been related to the mechanism of virus penetration in host cells (13)(14)(15); the current model supports the hypothesis that the acidification of endosomes, where FMDV virions are sorted, triggers viral uncoating and genome release (16)(17)(18).…”
Section: The Viral Capsid Protects the Viral Genome From Environmentamentioning
confidence: 99%
See 4 more Smart Citations
“…An intriguing feature of the FMDV capsid is the extreme sensitivity to acidic pH, which results in virus inactivation after exposure of virions to mildly acidic pH (8). At pH slightly below neutrality, FMDV capsid disassembles into pentameric subunits (9) and there is good correlation between loss of infectivity by in vitro exposure to acidic pH and capsid dissociation (10)(11)(12). The acid sensitivity of FMDV has been related to the mechanism of virus penetration in host cells (13)(14)(15); the current model supports the hypothesis that the acidification of endosomes, where FMDV virions are sorted, triggers viral uncoating and genome release (16)(17)(18).…”
Section: The Viral Capsid Protects the Viral Genome From Environmentamentioning
confidence: 99%
“…The analysis of these mutants revealed that the mechanism to escape the inhibitory effect of NH 4 Cl was based on the elevation of the uncoating pH (9, 13). On the other hand, point mutations in the viral capsid can enhance acid resistance by lowering the pH required for uncoating (11,12,(22)(23)(24). One such amino acid substitution, N17D, Citation Caridi F, Vázquez-Calvo A, Sobrino F, Martín-Acebes MA.…”
Section: The Viral Capsid Protects the Viral Genome From Environmentamentioning
confidence: 99%
See 3 more Smart Citations